A system-theoretic approach to safety and security co-analysis of autonomous ships - Zhou, Xiang-Yu; Liu, Zheng-Jiang; Wang, Feng-Wu; Wu, Zhao-Lin (Ocean engineering, 2021)
The autonomous ship carrying valuable cargoes and passengers in a more effective and cost-saving manner will soon be state of the art technology, which most likely shall be introduced into the public horizon as the remote control mode within the foreseeable future. The highly connected intelligent systems though come at the cost of the increased system vulnerability to cyber-attacks. To smooth this innovative system can be released into actual context of operation, a novel STPA-based methodology is proposed that synthesizes safety and security, namely STPA-SynSS. In the novel method, a comprehensive process to identifying hazards and revealing causal factors is provided, hazard elimination/mitigation strategies are implemented into system design via system safety and security requirements, so that hazards can be continually tracked and closed-loop managed. The insight regards the operations of the method was demonstrated in a remotely-controlled ship with seafarers onboard, the analysis process focused on encountering ship-ship collision accidents and related security incidents. Results indicate that generated inadvertent/intentional causal factors and developed elimination/mitigation strategies can assist the processes of design and operational planning of the autonomous ships and its shore control centre. Further, the proposed method of this paper also has general relevance for other intelligent systems. •Cyber-attacks have become one of the major challenges to ensure the system safety of autonomous ships.•A novel extension to the STPA framework is proposed to address the interdependencies of safety and security, namely STPA-SynSS.•The proposed method provides a comprehensive process for continuous tracking and closed-loop management of system hazards.•A hierarchical control structure for hazard analysis of a remotely-controlled ship with seafarers onboard is presented.•The outputs of causal factors and hazard control strategies can give a general reference for the developers of autonomous ships.